Lutein-loaded composite modified wheat gliadin nanoparticles as well as preparation and application of lutein-loaded composite modified wheat gliadin nanoparticles

Through enzymatic decomposition of enzymatic decomposition of wheat glutinin combined with glycosylation and low-temperature-high temperature cycle reaction, combined with ultrasonic technology, the lutein-complex modified wheat glutinin nanoparticles were prepared, which solved the protection effect of existing carriers on lutein The poor problem achieves efficient load and stability improvement, simplifying the preparation process.

CN119280183AActive Publication Date: 2025-01-10NORTHEAST AGRICULTURAL UNIVERSITY

Patent Information

Application Number
CN202411394760.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2025-01-10
Estimated Expiration
2044-10-08

AI Technical Summary

Technical Problem

The existing carrier has poor protective effect on lutein, long preparation cycle and complex operation, which limits its application in health care and food fields, especially the lack of stability of polysaccharide modified glycolin under strong alkaline and high temperatures. Causes poor load effect.

Method used

Enzymatically soluble wheat glycosylated combined with glycosylation modification was used to improve the grafting degree of dextran through low-temperature-high-temperature cycle reaction, and combined with ultrasonic technology to prepare lutein-complex modified wheat glycosylated nanoparticles, optimized Polysaccharide modification process of gliprotein to improve loading effect.

Benefits of technology

It significantly improves the encapsulation rate and stability of lutein, weakens the degree of browning, simplifies the preparation process, improves the preparation efficiency, and achieves efficient lutein loading and protection effects, with a load rate of 7.5 to 8.2%. , and maintain the stability of lutein under different environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119280183A_ABST
    Figure CN119280183A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of wheat gliadin drug-loaded nanoparticle processing, and particularly relates to lutein-loaded composite modified wheat gliadin nanoparticles as well as a preparation and application thereof. The composite modified wheat gliadin nanoparticles are modified by combining enzymolysis with dextran grafting, and the dextran grafting adopts a low-temperature-high-temperature circulation method, so that the grafting degree is remarkably improved, and the browning degree is relatively low. According to the lutein-loaded composite modified wheat gliadin nanoparticles, pH folding is combined with an ultrasonic method, so that the encapsulation efficiency of lutein is remarkably improved. The obtained nanoparticles can significantly improve the illumination and thermal stability of the nanoparticles and the stability in the gastrointestinal tract environment, are suitable for improving the oral utilization rate of xanthophyll, and are used for preparing oral drugs, oral health-care foods and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of processing wheat prolamin drug-loaded nanoparticles, and in particular relates to lutein-loaded composite modified wheat prolamin nanoparticles, preparations and uses thereof. Background Art

[0002] Lutein is a natural flavonoid compound widely found in daily diet, with antioxidant, antibacterial and anti-inflammatory effects. However, the poor stability, solubility and low bioavailability of lutein limit its application in the fields of health care and food. To this end, people have developed a variety of loading systems, such as solid dispersions, microemulsions, liposomes, polymer nanoparticles, etc. to improve the stability, solubility and bioavailability of lutein. However, the protective effects of these carriers on lutein vary greatly, and there are potential safety hazards after they are put into production and commercialization, which is not conducive to further promotion. In addition, the preparation cycle of various carriers is long, the steps are cumbersome, and the operation is complicated, which is not conducive to commercial continuous production.

[0003] Biomacromolecules of food matrix, such as proteins, can be used as carriers for lutein. However, natural proteins have their own properties that are insufficient. In order to improve their loading and protective properties, proteins are often modified, such as enzymatic modification or chemical modification (glycosylation or phosphorylation modification, etc.). Patent document CN114159409A provides a zein nanoparticle loaded with lutein. The zein is modified by enzymatic hydrolysis combined with glycosylation modification (glucosamine modification), which can improve the stability of lutein. Its glycosylation modification requires the use of transglutaminase.

[0004] Studies have shown that in the glycosylation modification of alcohol-soluble proteins, the harmful products of polysaccharide modification are lower than those of monosaccharides. However, when polysaccharide-modified alcohol-soluble proteins are used to load substances such as quercetin, rutin, ferulic acid, chlorogenic acid, rhubarb, capsaicin, and lutein, polysaccharide-modified alcohol-soluble proteins are usually modified under strong alkalinity and high temperature, while substances such as lutein have poor stability under strong alkalinity or high temperature conditions, making it a new technical problem for polysaccharide-modified alcohol-soluble proteins to effectively load unstable substances such as quercetin and lutein (Analysis of Factors Influencing the Formation of Harmful Products in the Glycosylation Modification of Wheat Alcohol-soluble Proteins, Food Science, 2017). In addition, when glucan is currently used to graft alcohol-soluble proteins, the grafting degree is often low (less than 20%, mostly around 10%), for example, "Effect of glucan molecular weight on the structure and emulsification of zein grafts" (Zhao Chengbin et al. Transactions of the Chinese Society of Agricultural Engineering, 2018; Dong Yanjiao), and the loading rate is low, usually around 3-6%.

[0005] Therefore, improving the polysaccharide modification process of alcohol-soluble proteins, enhancing the polysaccharide modification effect of alcohol-soluble proteins and the loading effect on unstable substances are the directions that still need to be optimized. Summary of the invention

[0006] In view of the above technical problems, the purpose of the present invention is to provide a lutein-loaded composite modified wheat prolamin nanoparticles and preparations and uses. To achieve the above purpose, the technical solution of the present invention is as follows:

[0007] A lutein-loaded composite modified wheat prolamin nanoparticle, the preparation method of which comprises the following steps:

[0008] S1 Preparation of enzymatically hydrolyzed wheat alcohol-soluble protein: Disperse the wheat alcohol-soluble protein with water, add alkaline protease for enzymatic hydrolysis, collect the supernatant by centrifugation, and freeze-dry to obtain the enzymatically hydrolyzed wheat alcohol-soluble protein;

[0009] S2 enzymatically hydrolyzed wheat alcohol-soluble protein glucan grafting: enzymatically hydrolyzed wheat alcohol-soluble protein is dispersed in water to prepare an enzymatically hydrolyzed wheat alcohol-soluble protein aqueous solution, and glucan is added at a mass ratio of enzymatically hydrolyzed wheat alcohol-soluble protein to glucan of (1-2):1, and firstly stirred in a 60°C water bath at a speed of 100xg-300xg for 20 minutes; then stirred in an 80°C water bath at a speed of 400xg-700xg for 10 minutes, which is regarded as a low-temperature-high-temperature cycle; after 3-10 low-temperature-high-temperature cycle reactions, the reaction is terminated, cooled, the pH is adjusted to 7.0, centrifuged and the supernatant is collected, and ultrafiltration centrifugation is performed in an ultrafiltration centrifuge tube to remove unreacted enzymatically hydrolyzed wheat alcohol-soluble protein and glucan, and the clear liquid after ultrafiltration is collected and freeze-dried to obtain a composite modified wheat alcohol-soluble protein;

[0010] Preparation of S3 drug-loaded nanoparticles: The composite modified wheat alcohol-soluble protein is dispersed in water to prepare a composite modified wheat alcohol-soluble protein aqueous solution, lutein is added in a ratio of 10:1 between the mass ratio of the composite modified wheat alcohol-soluble protein and lutein, the pH is adjusted to 11.0, ultrasonicated at 100W to 300W for 2min to 4min, the pH is adjusted to 7.0, the unencapsulated lutein is removed by centrifugation, the supernatant is collected, and lyophilized to obtain lutein-loaded composite modified wheat alcohol-soluble protein nanoparticles.

[0011] Preferably, in step S2, the molecular weight of the dextran is 2 kDa to 100 kDa, and more preferably, the molecular weight of the dextran is 6 kDa.

[0012] Preferably, in step S1, the reaction conditions of the enzymolysis are: the amount of alkaline protease added is 1000U / g wheat alcohol-soluble protein to 7000U / g wheat alcohol-soluble protein; the enzymolysis temperature is 40°C to 60°C; the enzymolysis pH is 8 to 10; and the enzymolysis time is 30min to 240min. Further preferably, in step S1, the reaction conditions of the enzymolysis are: the amount of alkaline protease added is 3000U / g wheat alcohol-soluble protein; the enzymolysis temperature is 55°C; the enzymolysis pH is 8.5; and the enzymolysis time is 60min.

[0013] Preferably, in step S1, the centrifugation condition is 4°C, 6000xg to 12000xg for 5min to 60min; more preferably, in step S1, the centrifugation is 8000xg for 20min.

[0014] Preferably, in step S2, the mass fraction of the enzymatically hydrolyzed wheat prolamin in the aqueous solution of enzymatically hydrolyzed wheat prolamin is 1%; in step S3, the mass fraction of the composite modified wheat prolamin in the aqueous solution of composite modified wheat prolamin is 1%.

[0015] Preferably, in step S2, the mass ratio of enzymatically hydrolyzed wheat prolamin to glucan is 1:1.

[0016] Preferably, in step S2, the low temperature-high temperature cycle reaction is repeated 6 to 8 times.

[0017] Preferably, in step S2, the ultrafiltration centrifugation conditions are: ultrafiltration centrifuge tube molecular weight cutoff 30 kDa, 4°C, 4000 x g centrifugation for 20 min.

[0018] Preferably, in step S2, the stirring speed of the 60°C water bath is 200 x g, and the stirring speed of the 80°C water bath is 500 x g.

[0019] Preferably, in step S3, the ultrasonic power is 200W.

[0020] Preferably, in step S3, the ultrasonic time is 4 minutes.

[0021] Preferably, in step S3, the centrifugation conditions are: 4°C, 8000xg for 10 min.

[0022] An oral preparation is prepared from the aforementioned lutein-loaded composite modified wheat alcohol-soluble protein nanoparticles and auxiliary materials.

[0023] Preferably, the auxiliary material is water.

[0024] Use of the aforementioned lutein-loaded composite modified wheat alcohol-soluble protein nanoparticles or oral preparations in the preparation of medicines or health foods.

[0025] Beneficial effects of the present invention:

[0026] (1) The present invention uses wheat alcohol-soluble protein as raw material, and its production raw material gluten is a by-product of wheat starch separation and processing, and is low in price.

[0027] (2) The present invention aims to solve the problems of poor solubility of wheat alcohol-soluble protein and weak encapsulation ability in aqueous systems by combining enzymatic hydrolysis with glycosylation reaction to improve the structure and functional properties of wheat alcohol-soluble protein; and construct nanoparticles loaded with lutein to improve the encapsulation effect and stability of lutein.

[0028] (3) The present invention adopts a low-temperature-high-temperature cycle heating method to carry out the glucan glycosylation reaction of alcohol-soluble protein, thereby increasing the grafting degree between protein and polysaccharide, reducing the degree of browning, and being beneficial to increasing the drug loading capacity (encapsulation rate and loading rate) of nanoparticles and improving the appearance of the preparation and process stability. The mass ratio of modified alcohol-soluble protein to lutein can be as low as 10:1, and the lutein encapsulation rate can reach 75-82%, that is, the lutein loading rate can reach 7.5-8.2% (lutein loading rate is the percentage of encapsulated lutein / modified alcohol-soluble protein).

[0029] (4) The present invention combines the pH folding method with the ultrasonic method to prepare lutein-loaded nanoparticles, so that the traditional long-time stirring method is replaced by a short-time ultrasonic process, which saves preparation time and improves preparation efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 The transmission electron microscopy image and particle size distribution diagram of lutein-loaded composite modified wheat alcohol-soluble protein nanoparticles;

[0031] Figure 2 This is the result diagram of the effect of storage time on the degradation degree of lutein;

[0032] Figure 3 This is the result diagram of the effect of light exposure time on the degree of lutein degradation;

[0033] Figure 4 This is the result diagram of the effect of heating time on the degradation degree of lutein;

[0034] Figure 5 This is a graph showing the effect of in vitro digestion on the bioavailability of lutein; DETAILED DESCRIPTION

[0035] The present invention is further described in detail below in conjunction with specific embodiments and drawings. Except for the contents specifically mentioned below, the processes, conditions, reagents and experimental methods for implementing the present invention are common knowledge and common common sense in the art and are not particularly limited in the present invention.

[0036] The reagents used in the following examples of the present invention are as follows:

[0037] Alkaline protease was purchased from Shanghai Yuanye Biotechnology Co., Ltd.;

[0038] Dextran was purchased from Macklin Co., Ltd., with a molecular weight of 6 kDa;

[0039] Artificial gastric juice was purchased from Regen Biotechnology;

[0040] Wheat gluten was purchased from Shanghai Xintai Industrial Co., Ltd.;

[0041] Lyophilized lutein powder (purity 80%) was purchased from Shanghai Xianding Biotechnology Co., Ltd.

[0042] The detection method involved in the present invention is as follows:

[0043] 1. Determination of hydrolysis degree

[0044] The pH-state method was used to calculate the degree of hydrolysis (DH) of the protein hydrolysate according to the volume of NaOH consumed during the reaction. The specific calculation formula is:

[0045]

[0046] In the formula, B represents the volume of NaOH consumed (mL), N B represents the concentration of NaOH (mol / L), M p represents the mass of added protein (g), h tot represents the theoretical amount of peptide bonds per unit mass of protein (8.03mmol / g), α represents the degree of dissociation of amino acids, which can be calculated using the following formula, and the pK value is obtained according to the Gibbs-Helmholz equation:

[0047]

[0048] 2. Determination of grafting degree

[0049] The degree of grafting was determined by the o-phthalaldehyde method (OPA). 80 mg of o-phthalaldehyde (OPA) was completely dissolved in 2 mL of methanol and mixed with 50 mL of 0.1 mol / L sodium tetraborate buffer (pH 9.7), 200 μL of β-mercaptoethanol and 5 mL of 200 mg / mL dodecyl sulfate (SDS) solution. The volume of the solution was adjusted to 100 mL with distilled water and the OPA reagent was prepared as needed. When determining the degree of grafting, 100 μL of the sample solution (5 mg / mL) was thoroughly mixed with 4 mL of the OPA reagent, placed in a constant temperature water bath at 35°C in a dark place, and reacted for 2 minutes. The absorbance of the sample was measured at 340 nm, and distilled water was used as the blank solution.

[0050]

[0051] Wherein, A represents the absorbance of modified wheat alcohol-soluble protein at 340nm, A t Represents the absorbance of the sample at 340 nm.

[0052] 3. Determination of browning degree

[0053] The protein solution was diluted with a 0.1% SDS solution to a protein concentration of 0.2% and the absorbance value A was measured at a wavelength of 420 nm. 420The absorbance is proportional to the browning of the protein.

[0054] 4. Determination of Encapsulation Efficiency

[0055] Methanol was used to prepare lutein solutions with concentrations of 10, 15, 20, 25, and 30 μg / mL, and the absorbance of the samples at 445 nm was measured to draw a standard curve. The precipitate (containing unencapsulated lutein) after centrifugation in the preparation step of drug-loaded nanoparticles was mixed with 10 mL of methanol, vortexed for 5 min in the dark, centrifuged at 4°C, 10000xg for 30 min, and the supernatant was taken for determination. The lutein content was determined by high performance liquid chromatography (U3000, Thermo Fisher Scientific, America), and the specific chromatographic conditions were: the chromatographic column was a C30 column (4.6 mm × 250 mm, 5 μm), the column temperature was 35°C; the mobile phase was methanol / water (volume ratio 95:5, containing 0.1% butylated hydroxytoluene), isocratic elution was used, the flow rate was 1.0 mL / min, the detection wavelength was 445 nm, and the injection volume was 50 μL.

[0056] The lutein concentration was calculated based on the standard curve. The lutein encapsulation efficiency was calculated according to the following formula:

[0057]

[0058] 5. Determination of Lutein Stability

[0059] A lutein methanol solution (1 mL) with a concentration of 4 mg / mL was mixed with 24 mL of deionized water as free lutein (ie, a control substance without nanoparticle loading).

[0060] (1) Determination of storage stability

[0061] The same volume of free lutein and lutein-loaded nanoparticle solution were stored together at 4°C for 30 days, and the residual lutein content in the solution was measured every 6 days. The storage stability of lutein was evaluated by measuring the change in lutein content.

[0062] (2) Determination of photostability

[0063] At room temperature, the same volume of free lutein and loaded lutein nanoparticle solution was irradiated under a HR-XD-150 xenon lamp for 180 min. The light intensity of the lamp was 0.5 W / m 2 The distance between the sample and the lamp was fixed at 40 cm. A certain amount of sample was taken every 30 minutes to determine the residual lutein content. The light stability of lutein was evaluated by measuring the change in lutein content.

[0064] (3) Determination of thermal stability

[0065] The same volume of free lutein and loaded lutein nanoparticle solution were heated together at 90°C for 180 minutes. A certain amount of sample was taken every 30 minutes, immediately cooled to room temperature, and the residual lutein content was measured. The thermal stability of lutein was evaluated by measuring the change in lutein content.

[0066] The method for determining the residual lutein content is as follows: 1 mL of free lutein / lutein-loaded nanoparticle solution is mixed with 4 mL of methanol, vortexed for 5 minutes in the dark, centrifuged at 4°C, 10,000 x g for 30 minutes, and the supernatant is taken for determination. The lutein content in the solution is determined by high performance liquid chromatography, and the determination method is the same as the encapsulation rate. The calculation method of the lutein retention rate is as follows:

[0067]

[0068] 5. Simulated in vitro digestion

[0069] 20 mL of lutein-loaded nanoparticles and free lutein solution were mixed with 20 mL of simulated gastric fluid (mainly containing 3.2 mg / mL pepsin, 2 mg / mL NaCl and 7 mL / L concentrated hydrochloric acid), and the pH of the solution was adjusted to 2.0 using 1 mol / L HCl. The mixture was stirred at 37°C and 300 x g for 120 min to simulate the gastric digestion process (SGF). After gastric digestion, the pH of the solution was adjusted to 7.5 for intestinal digestion.

[0070] Prepare 20 mL of simulated intestinal fluid (6.8 mg / mL K 2 HPO 4 , 0.8 mg / mL trypsin, 20 mg / mL bile extract and 8.775 mg / mL NaCl were mixed for later use. The mixture after gastric digestion was mixed with an equal volume of simulated intestinal fluid, the pH of the solution was adjusted to 7.5 using 1 mol / L NaOH, and stirred at 37°C, 300xg for 120 min to simulate the intestinal digestion process (SIF). After the intestinal digestion was completed, the digestive fluid was placed in a boiling water bath for 10 min to inactivate the digestive enzymes. During the simulated gastric and intestinal digestion, 3 mL of digestive fluid was collected every 30 min for subsequent determination.

[0071] The collected gastric digestive juice and intestinal digestive juice were heated at 90°C for 5 minutes to inactivate the digestive enzymes. The digestive juice was cooled to room temperature, centrifuged at 10,000 x g for 30 minutes, and the micellar phase was taken for determination. The total amount of lutein in the micellar phase was determined by the SDS dissociation method. 2 mL of SDS (1.5 mol / L) was mixed with 0.5 mL of the micellar phase and vortexed for 2 minutes. The total volume of each mixed solution was diluted to 10 mL with deionized water, and allowed to stand at room temperature for 30 minutes. The absorbance of the supernatant at 446 nm was determined by a UV-2700 ultraviolet-visible spectrophotometer, and the lutein concentration was calculated according to the standard curve. The bioavailability of lutein was calculated as follows:

[0072]

[0073] The preparation method of wheat prolamin used in the embodiment of the present invention is as follows:

[0074] Wheat gluten powder was mixed with dichloromethane at a solid-liquid ratio of 1 g:7 mL, stirred continuously for 2 h, and dichloromethane was removed by vacuum filtration, and the above defatting process was repeated twice. Defatted gluten powder was mixed with 70% ethanol aqueous solution at a solid-liquid ratio of 1 g:10 mL, stirred for 3 h, centrifuged at 4 ° C, 9000 x g for 10 min, the supernatant was collected, the ethanol was removed by rotary evaporation, and the obtained suspension was freeze-dried to obtain wheat alcohol-soluble protein freeze-dried powder.

[0075] The preparation method of enzymatically hydrolyzed wheat prolamin used in the embodiment of the present invention is as follows:

[0076] The wheat prolamin freeze-dried powder was mixed with distilled water to prepare a wheat prolamin dispersion with a mass fraction of 1%. Based on the mass of the wheat prolamin freeze-dried powder, 3000U / g of alkaline protease was added to the wheat prolamin freeze-dried powder. The mixture was enzymolyzed at 55°C and pH 8.5 for 60 minutes. The supernatant was collected by centrifugation and freeze-dried to obtain the enzymolyzed wheat prolamin.

[0077] Example 1: Effect of low-temperature-high-temperature cycles on enzymatic wheat prolamin grafting

[0078] The enzymatically hydrolyzed wheat alcohol-soluble protein was mixed with distilled water to prepare a modified wheat alcohol-soluble protein aqueous solution with a mass fraction of 1%, and glucan was added to make the mass ratio of modified wheat alcohol-soluble protein to glucan 1:1, and the pH was adjusted to 8.0. The mixture was stirred for 2 hours, and then a continuous cycle glycosylation reaction was carried out. The specific operation process is as follows: first, the mixed solution was placed in a 60°C water bath and stirred at a speed of 200xg for 20 minutes; secondly, the solution was placed in an 80°C water bath and reacted at a speed of 500xg for 10 minutes, which was regarded as one cycle. After 3-8 cycles, the reaction was immediately cooled after the reaction was completed, the pH of the sample solution was adjusted to 7.0, centrifuged and the supernatant was collected. The supernatant was centrifuged in an ultrafiltration centrifuge tube with a molecular weight cutoff of 30kDa, and centrifuged at 4°C, 4000xg, for 20 minutes to remove the unreacted modified wheat alcohol-soluble protein and glucan. The ultrafiltration clear liquid was collected and freeze-dried to obtain composite modified wheat alcohol-soluble protein nanoparticles.

[0079] Table 1 Effect of cycle number on grafting degree and browning degree of composite modified wheat prolamin

[0080]

[0081]

[0082] Note: Lowercase letters (af) represent significant differences in the effect of the number of cycles on the grafting degree and browning degree of the composite modified wheat prolamin

[0083] As shown in Table 1, with the increase of the number of cycles, the degree of glucan grafting is significantly improved, and when the number of cycles reaches 6 or more, the degree of glucan grafting exceeds 20%, while the degree of browning is still less than 0.07%.

[0084] The grafting degree increases with the increase of the number of reaction cycles, and the highest value is 24.4% when the cycle is 7 times. It can be seen that the use of low temperature and low stirring speed can prevent protein aggregation, but glycosylation reaction can still occur. The second step of the cycle requires heating at 80°C for 10 minutes. The shorter heating time can prevent excessive aggregation of proteins and accelerate the glycosylation reaction, which can significantly improve the grafting efficiency.

[0085] Example 2 Effect of reaction temperature and time on enzymatic wheat prolamin grafting

[0086] In order to investigate the effect of low-temperature-high-temperature cycle temperature and time on enzymatic wheat prolamin grafting, the following control samples were prepared for control experiments:

[0087] Control 1: Continuous glycosylation reaction at 60°C: Mix enzymatically hydrolyzed wheat alcohol-soluble protein with distilled water to prepare a modified wheat alcohol-soluble protein aqueous solution with a mass fraction of 1%, add glucan, so that the mass ratio of modified wheat alcohol-soluble protein to glucan is 1:1, adjust the pH to 8.0, and stir together for 2h. Place the mixed solution in a 60°C water bath and continue stirring at a speed of 500xg for 1 to 5. Cool immediately after the reaction, adjust the pH of the sample solution to 7.0, centrifuge and collect the supernatant. Centrifuge the supernatant in an ultrafiltration centrifuge tube with a molecular weight cutoff of 30kDa, centrifuge at 4°C, 4000xg, and centrifuge for 20min to remove unreacted modified wheat alcohol-soluble protein and glucan. Collect the ultrafiltration clear liquid and freeze-dry it to obtain the composite modified wheat alcohol-soluble protein.

[0088] Control 2: Continuous glycosylation reaction at 80°C: Mix the enzymatically hydrolyzed wheat alcohol-soluble protein with distilled water to prepare a modified wheat alcohol-soluble protein aqueous solution with a mass fraction of 1%, add dextran with a molecular weight of 6kDa, so that the mass ratio of modified wheat alcohol-soluble protein to dextran is 1:1, adjust the pH to 8.0, and stir together for 2h. Place the mixed solution in a 60°C water bath and stir continuously at a speed of 500xg for 1 to 5h. Cool immediately after the reaction, adjust the pH of the sample solution to 7.0, centrifuge and collect the supernatant. Centrifuge the supernatant in an ultrafiltration centrifuge tube with a molecular weight cutoff of 30kDa, centrifuge at 4°C, 4000xg, and centrifuge for 20min to remove unreacted modified wheat alcohol-soluble protein and dextran. Collect the ultrafiltration clear liquid, freeze-dry, and obtain the composite modified wheat alcohol-soluble protein.

[0089] Table 2 Effects of different reaction temperatures and times on the grafting degree and browning degree of composite modified wheat prolamin

[0090]

[0091] Note: Lowercase letters (ae) represent significant differences in the effects of different reaction temperatures and times on the grafting degree and browning degree of the composite modified wheat prolamin

[0092] As shown in Table 2, by comparison, it was found that when the glycosylation reaction was continued at 60°C and 80°C, the maximum grafting degree was reached at 4 hours, and the grafting degree was less than 20%. In addition, the continued reaction at a high temperature of 80°C resulted in a large degree of browning of the product (close to 0.1%), and too many intermediate substances were produced, which may affect the properties and results of the protein. As shown in Table 1, the low-temperature-high-temperature cycle better inhibited the occurrence of browning and was an efficient and favorable reaction method.

[0093] Example 3 Preparation of Lutein-Carrying Composite Modified Wheat Prolamin Nanoparticles

[0094] The composite modified wheat prolamin used in this example was prepared according to Example 1, and the number of cycles was 7 times.

[0095] (1) Determination of ultrasonic power

[0096] The composite modified wheat alcohol-soluble protein was mixed with distilled water to prepare a composite modified wheat alcohol-soluble protein aqueous solution with a mass fraction of 1%; a certain amount of lutein was added to the solution to make its mass concentration 0.1%, and the pH was adjusted to 11.0. The solution was ultrasonically treated with an ultrasonic device, the ultrasonic power was set to 100-400W, the ultrasonic time was 4min, and the pH was adjusted to 7.0. The sample was centrifuged at 4°C and 8000xg for 10min to remove the unencapsulated lutein. The supernatant was collected and freeze-dried to obtain lutein-loaded composite modified wheat alcohol-soluble protein nanoparticles.

[0097] Table 3 Effect of different ultrasonic powers on the encapsulation efficiency of lutein

[0098]

[0099]

[0100] Note: Lowercase letters (ad) represent significant differences in the effects of different ultrasonic powers on the encapsulation efficiency of lutein

[0101] As shown in Table 3 (in Table 3, the ultrasonic power is 0, i.e., no ultrasonic treatment is used, and conventional stirring is used at 500xg for 4 minutes), increasing the ultrasonic power can significantly increase the encapsulation rate of lutein. When the ultrasonic power is 200W, the encapsulation rate is the highest. When the ultrasonic power is increased to 400W, the encapsulation rate decreases. Therefore, taking the encapsulation rate of lutein as the evaluation index, the preferred ultrasonic power is 100-300W, and the best is 200W.

[0102] (2) Determination of ultrasound time

[0103] The composite modified wheat alcohol-soluble protein was mixed with distilled water to prepare a composite modified wheat alcohol-soluble protein aqueous solution with a mass fraction of 1%; a certain amount of lutein was added to the solution to make its mass concentration 0.1%, and the pH was adjusted to 11.0. The solution was ultrasonically treated with an ultrasonic device, the ultrasonic power was set to 200W, the ultrasonic time was 1 to 5 minutes, and the pH was adjusted to 7.0. The sample was centrifuged at 4°C and 8000xg for 10 minutes to remove the unencapsulated lutein. The supernatant was collected and freeze-dried to obtain lutein-loaded composite modified wheat alcohol-soluble protein nanoparticles.

[0104] Table 4 Effect of different ultrasound times on the encapsulation efficiency of lutein

[0105] Ultrasonic time (min) Encapsulation rate (%) 0 <![CDATA[51.3±0.2 d ]]> 1 <![CDATA[73.4±0.2 c ]]> 2 <![CDATA[78.5±0.1 b ]]> 3 <![CDATA[80.2±0.1 a ]]> 4 <![CDATA[81.3±0.5 a ]]> 5 <![CDATA[74.3±0.2 c ]]>

[0106] Note: Lowercase letters (ad) represent significant differences in the effects of different ultrasound times on the encapsulation efficiency of lutein.

[0107] As shown in Table 4 (in Table 4, the ultrasonic power is 0, that is, no ultrasonic treatment is used, and conventional stirring is used at a speed of 500xg for 4 minutes), as the ultrasonic time increases, the encapsulation rate of lutein increases, and when the ultrasonic time is 4 minutes, the encapsulation rate is the highest. When the ultrasonic power is increased to 5 minutes, the encapsulation rate decreases significantly. Therefore, taking the encapsulation rate of lutein as the evaluation index, the preferred ultrasonic time is 2 to 4 minutes, and the best is 4 minutes.

[0108] According to the experimental results, when the ultrasonic power is 200W and the ultrasonic time is 4min, the encapsulation rate of lutein is 81.3±0.5%. The transmission electron microscopy and particle size distribution of lutein-loaded composite modified wheat alcohol-soluble protein nanoparticles are shown in Figure 2. Figure 1 As shown, the nanoparticles present a uniformly dispersed spherical structure, and their particle sizes are between 50 and 100 nm.

[0109] As a control, the present invention carried out 2 groups of control experiments:

[0110] Control 1: The composite modified wheat alcohol-soluble protein was mixed with distilled water to prepare a composite modified wheat alcohol-soluble protein aqueous solution with a mass fraction of 1%; a certain amount of lutein was added to the solution to make its mass concentration 0.1%, the pH was adjusted to 11.0, stirred at a speed of 500xg for 4 minutes, and then the pH was adjusted to 7.0. The sample was centrifuged at 4°C and 8000xg for 10 minutes to remove the unencapsulated lutein. The supernatant was collected and freeze-dried to obtain lutein-loaded composite modified wheat alcohol-soluble protein nanoparticles.

[0111] Control 2: The composite modified wheat alcohol-soluble protein was mixed with distilled water to prepare a composite modified wheat alcohol-soluble protein aqueous solution with a mass fraction of 1%; a certain amount of lutein was added to the solution to make its mass concentration 0.1%, the pH was adjusted to 7.0, and the solution was ultrasonically treated with an ultrasonic device, the ultrasonic power was set to 200W, and the ultrasonic time was 4min. The sample was centrifuged at 4°C and 8000xg for 10min to remove the unencapsulated lutein. The supernatant was collected and freeze-dried to obtain lutein-loaded composite modified wheat alcohol-soluble protein nanoparticles.

[0112] The encapsulation rate of lutein obtained by control 1 was 51.3±0.2%, and the encapsulation rate of lutein obtained by control 2 was 30.2±0.5%, both of which were significantly lower than the encapsulation rate of the product obtained by the preparation method of the present invention (81.3±0.5%). This shows that the effect of simply using pH shift or physical methods on improving the lutein loading rate is limited, and the protein itself needs to be processed more deeply.

[0113] Example 4: Environmental stability of lutein

[0114] The lutein-loaded composite modified wheat prolamin nanoparticles of this embodiment were prepared by the method of Example 3 (ultrasonic power 200 W, ultrasonic time 4 min; pH adjusted to 11.0 before ultrasonication, pH adjusted to 7.0 after ultrasonication). The lutein-loaded composite modified wheat prolamin nanoparticle solution and the free lutein solution (preparation: 1 mL of lutein methanol solution with a concentration of 4 mg / mL was mixed with 24 mL of deionized water as the free lutein solution, i.e., the control substance without nanoparticle loading) were taken for stability study under the same conditions.

[0115] Figure 2 The effect of storage time on the stability of lutein at 4°C is shown. As shown in the figure, the stability of free lutein gradually decreases with time. After 30 days of storage, the retention rate of lutein in the control group (i.e., the content of lutein retained in the sample) decreased significantly to 50.3±0.6%. Lutein-loaded composite modified wheat alcohol-soluble protein nanoparticles can increase the lutein retention rate to 96.4±0.9%. The results show that the nanoparticles prepared by composite modified wheat alcohol-soluble protein have a good encapsulation effect on lutein and can protect lutein from environmental influences.

[0116] Due to the presence of polyphenols and unsaturated double bonds in the lutein structure, it is easily decomposed under ultraviolet light. Figure 3 The effect of light irradiation time on the stability of lutein was demonstrated. As shown in the figure, after 180 minutes of irradiation, the retention rate of lutein was 65.2±3.2%, and the retention rate of lutein in nanoparticles was 82.4±2.5%. The results show that the nanoparticle loading system protects lutein from the effects of ultraviolet radiation to a large extent.

[0117] Figure 4 The effect of different heating times at 90°C on the stability of lutein is shown. As shown in the figure, after heating at 90°C for 180 minutes, the retention rate decreased to 35.2±3.2%. Nanoparticles can effectively improve the thermal stability of lutein, and the retention rate of lutein is 63.2±0.9%. The results show that encapsulating lutein in nanoparticles is an effective means to improve its thermal stability, mainly due to the presence of more hydrogen bonds in nanoparticles.

[0118] In summary, the composite modified wheat prolamin nanoparticles can achieve efficient encapsulation of lutein and maintain its stability under different environments.

[0119] Example 5: Analysis of the effect of nanoparticles on lutein bioavailability

[0120] The lutein-loaded composite modified wheat prolamin nanoparticle solution of this example was prepared by the method of Example 3 (ultrasonic power 200 W, ultrasonic time 4 min, pH adjusted to 11.0 before ultrasonication, pH adjusted to 7.0 after ultrasonication). Free lutein solution was used as a control (prepared in the same manner as in Example 4).

[0121] During intestinal digestion, hydrophobic bioactive components can combine with bile salts and lipids to form mixed micelles, and the hydrophobic bioactive substances dissolved in the micelle phase pass through the small intestinal cells and are absorbed. The present invention evaluates the bioavailability of lutein by measuring the lutein remaining in the micelle phase at the end of in vitro simulated gastrointestinal digestion.

[0122] Lutein-loaded composite modified wheat alcohol-soluble protein nanoparticles and lutein were subjected to continuous gastric (2 h) and intestinal (2 h) digestion to determine the effect of nanoparticle encapsulation on the bioavailability of lutein.

[0123] like Figure 5 As shown in the results, after continuous gastric (2h) and intestinal (2h) digestion, the bioavailability of free lutein was only 19.4±0.6%, while the bioavailability of lutein in nanoparticles was 50.9±1.0%. The results showed that encapsulating lutein in nanoparticles significantly improved the absorption and utilization of lutein in the intestine, and the improvement effect of composite modified wheat alcohol-soluble protein nanoparticles was better.

[0124] Although the present invention has been disclosed as above with preferred embodiments, it is not intended to limit the present invention. Anyone familiar with the technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention should be based on the definition of the claims.

Claims

1. A lutein-loaded composite modified wheat prolamin nanoparticle, characterized in that: The preparation method of the nanoparticles comprises the following steps: S1 Preparation of enzymatically hydrolyzed wheat alcohol-soluble protein: Disperse the wheat alcohol-soluble protein with water, add alkaline protease for enzymatic hydrolysis, collect the supernatant by centrifugation, and freeze-dry to obtain the enzymatically hydrolyzed wheat alcohol-soluble protein; S2 enzymatically hydrolyzed wheat alcohol-soluble protein glucan grafting: enzymatically hydrolyzed wheat alcohol-soluble protein is dispersed in water to prepare an enzymatically hydrolyzed wheat alcohol-soluble protein aqueous solution, and glucan is added at a mass ratio of enzymatically hydrolyzed wheat alcohol-soluble protein to glucan of (1-2):1, and firstly reacted in a 60°C water bath at a speed of 100xg-300xg-stirring for 20min; then stirred in an 80°C water bath at a speed of 400xg-700xg for 10min, which is regarded as a low-temperature-high-temperature cycle; after 3-10 low-temperature-high-temperature cycle reactions, the reaction is terminated, cooled, the pH is adjusted to 7.0, centrifuged and the supernatant is collected, and ultrafiltration centrifugation is performed in an ultrafiltration centrifuge tube to remove unreacted enzymatically hydrolyzed wheat alcohol-soluble protein and glucan, and the clear liquid after ultrafiltration is collected and freeze-dried to obtain a composite modified wheat alcohol-soluble protein; Preparation of S3 drug-loaded nanoparticles: The composite modified wheat alcohol-soluble protein is dispersed in water to prepare a composite modified wheat alcohol-soluble protein aqueous solution, lutein is added in a ratio of 10:1 between the mass ratio of composite modified wheat alcohol-soluble protein and lutein, the pH is adjusted to 11.0, ultrasound is applied at 100W~300W for 2min~4min, the pH is adjusted to 7.0, and the unencapsulated lutein is removed by centrifugation. The supernatant is collected and freeze-dried to obtain lutein-loaded composite modified wheat alcohol-soluble protein nanoparticles.

2. The lutein-loaded composite modified wheat prolamin nanoparticles according to claim 1, characterized in that: In step S1, the reaction conditions of the enzymolysis are: the addition amount of alkaline protease is 1000U / g wheat alcohol-soluble protein to 7000U / g wheat alcohol-soluble protein; the enzymolysis temperature is 40°C to 60°C; the enzymolysis pH is 8 to 10; and the enzymolysis time is 30min to 240min.

3. The lutein-loaded composite modified wheat prolamin nanoparticles according to claim 1, characterized in that: In step S1, the centrifugation condition is 4°C, 6000xg~12000xg for 5min~60min.

4. The lutein-loaded composite modified wheat prolamin nanoparticles according to claim 1, characterized in that: In step S2, the molecular weight of the dextran is 2 kDa~100 kDa.

5. The lutein-loaded composite modified wheat prolamin nanoparticles according to claim 1, characterized in that: In step S2, the mass fraction of the enzymatically hydrolyzed wheat prolamin in the aqueous solution of enzymatically hydrolyzed wheat prolamin is 1%; in step S3, the mass fraction of the composite modified wheat prolamin in the aqueous solution of composite modified wheat prolamin is 1%.

6. The lutein-loaded composite modified wheat prolamin nanoparticles according to claim 1, characterized in that: In step S2, the mass ratio of the enzymatically hydrolyzed wheat prolamin to glucan is 1:

1.

7. The lutein-loaded composite modified wheat prolamin nanoparticles according to claim 1, characterized in that: In step S2, the low temperature-high temperature cycle reaction is repeated 6 to 8 times.

8. The lutein-loaded composite modified wheat prolamin nanoparticles according to claim 1, characterized in that: In step S2, the ultrafiltration centrifugation conditions are: ultrafiltration centrifuge tube molecular weight cutoff 30kDa, 4°C, 4000xg centrifugation for 20min.

9. The lutein-loaded composite modified wheat prolamin nanoparticles according to claim 1, characterized in that: In step S2, the stirring speed of the 60°C water bath is 200xg, and the stirring speed of the 80°C water bath is 500xg.

10. The lutein-loaded composite modified wheat prolamin nanoparticles according to claim 1, characterized in that: In step S3, the ultrasonic power is 200W.

11. The lutein-loaded composite modified wheat prolamin nanoparticles according to claim 1, characterized in that: In step S3, the ultrasonic time is 4 minutes.

12. The lutein-loaded composite modified wheat prolamin nanoparticles according to claim 1, characterized in that: In step S3, the centrifugation conditions are: 4°C, 8000xg for 10 min.

13. An oral preparation, characterized in that: The invention is prepared from the lutein-loaded composite modified wheat alcohol-soluble protein nanoparticles according to any one of claims 1 to 13 and auxiliary materials.

14. Use of the lutein-loaded composite modified wheat prolamin nanoparticles according to any one of claims 1 to 12 or the oral preparation according to claim 13 in the preparation of medicines or health foods.

Citation Information

Patent Citations

  • Preparation method and device of glycosylation zein nano-carrier

    CN106420666A

  • Protein particle with core-shell structure as well as preparation method and application of protein particle

    CN113599367A

  • Preparation method of glycosylated corn protein polypeptide carried xanthophyll nanoparticles

    CN114159409A

  • Aming Ring

    KR102753991B1

  • Protein nanocarriers for topical delivery

    US20120195947A1

Cited By

  • Alkali-induced glycosylation tilapia protein hydrolysate loaded with fat-soluble polyphenol as well as preparation method and application of alkali-induced glycosylation tilapia protein hydrolysate

    CN121058875A

  • Alkali-induced glycosylation of rohu protein hydrolysate loaded with fat-soluble polyphenols, and preparation method and application thereof

    CN121058875B